2010
DOI: 10.1111/j.1551-2916.2010.03740.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Sintering of Multilayer Integrated Passive Devices

Abstract: Microwave sintering of multilayer capacitor/varistor‐based integrated passive devices (IPDs) has been investigated for the first time. The sintered samples were characterized for density, microstructure, composition, and electrical performance. It was found that IPDs with varistor/capacitor formulations could be microwave sintered to fully dense device components within 3 h of total cycle time, which is <1/10th of the time required by conventional methods. Microwave sintering resulted in products with a finer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…For example, research on the firing of zinc oxide varistors yielded results that showed that hybrid sintered devices exhibited more homogeneous and finer microstructures that exhibited superior electrical properties [15]. In addition, the combination of hybrid heating with a new firing strategy known as two stage sintering [16] has yielded the ability to achieve nanostructured zirconia with densities >99.5% of theoretical whilst retaining final average grain sizes as fine as just 65 nm using precursor nanopowders with an average grain size of ~16 nm [17], figure 3.…”
Section: Mixing In High Loss Additivesmentioning
confidence: 99%
“…For example, research on the firing of zinc oxide varistors yielded results that showed that hybrid sintered devices exhibited more homogeneous and finer microstructures that exhibited superior electrical properties [15]. In addition, the combination of hybrid heating with a new firing strategy known as two stage sintering [16] has yielded the ability to achieve nanostructured zirconia with densities >99.5% of theoretical whilst retaining final average grain sizes as fine as just 65 nm using precursor nanopowders with an average grain size of ~16 nm [17], figure 3.…”
Section: Mixing In High Loss Additivesmentioning
confidence: 99%
“…Therefore, much higher heating rates are achievable with microwaves, which is one of the most important factors in many processes. Along with the evident energy savings and reduction in process duration, high rates of microwave heating can help improve the product quality, resulting in the final materials with finer and less defective microstructures and enhanced functional properties . The role of high heating rates in densification enhancement has been demonstrated in other field‐assisted techniques, such as spark plasma sintering …”
Section: Introductionmentioning
confidence: 99%
“…This is an important advance in terms of energy saving and reduction in process duration and, consequently, of the economic cost. This can help to improve the product quality, resulting in the final materials with finer and less defective microstructures and enhanced functional and structural properties [29].…”
Section: Fig 3 Represents the Fe-sem Fracture Surface Of Las Samplesmentioning
confidence: 99%